Simulation and genetic optimization of control systems by LabVIEW programming - Zherebko, V.A.; Pisarenko, O.A.; Drabynko, V.P. (Інститут програмних систем НАН України, 2018)
The procedures for the engineering, synthesis, simulation and targeted implementation of algorithms for solving optimization problems in hierarchical automated control systems require complex objects using a variety of mathematical and software and hardware for research and engineering work. In this article the unification of mathematical and algorithmic support in the form of a unified concept of solving optimal control is proposed. We propose to use LabVIEW software and CompactRIO industrial controller as the unification of software and hardware implementation of mathematical-algorithmic developments, on which developed software tools to solve optimization problems using genetic algorithm.Problems in programming 2018; 2-3: 288-295